Regularized-renormalized-resummed loop corrected power spectrum of non-singular bounce with Primordial Black Hole formation - Sayantan Choudhury; Ahaskar Karde; Sudhakar Panda; Soumitra SenGupta (European Physical Journal C: Particles and Fields)
Abstract We present a complete and consistent exposition of the regularization, renormalization, and resummation procedures in the setup of having a contraction and then non-singular bounce followed by inflation with a sharp transition from slow-roll (SR) to ultra-slow roll (USR) phase for generating primordial black holes (PBHs). We consider following an effective field theory (EFT) approach and study the quantum loop corrections to the power spectrum from each phase. We demonstrate the complete removal of quadratic UV divergences after renormalization and softened logarithmic IR divergences after resummation and illustrate the scheme-independent nature of our renormalization approach. We further show that the addition of a contracting and bouncing phase allows us to successfully generate PBHs of solar-mass order, $$M_PBH\sim \mathcal{O}(M_{\odot })$$ M PBH ∼ O ( M ⊙ ) , by achieving the minimum e-folds during inflation to be $$Δ N_{Total}\sim \mathcal{O}(60)$$ Δ N Total ∼ O ( 60 ) and in this process successfully evading the strict no-go theorem. We notice that varying the effective sound speed between $$0.88\leqslant c_{s}\leqslant 1$$ 0.88 ⩽ c s ⩽ 1 , allows the peak spectrum amplitude to lie within $$10^{-3}\leqslant A \leqslant 10^{-2}$$ 10 - 3 ⩽ A ⩽ 10 - 2 , indicating that causality and unitarity remain protected in the theory. We analyse PBHs in the extremely small, $$M_{PBH}\sim \mathcal{O}(10^{-33}-10^{-27})M_{\odot }$$ M PBH ∼ O ( 10 - 33 - 10 - 27 ) M ⊙ , and the large, $$M_{PBH}\sim \mathcal{O}(10^{-6}-10^{-1})M_{\odot }$$ M PBH ∼ O ( 10 - 6 - 10 - 1 ) M ⊙ , mass limits and confront the PBH abundance results with the latest microlensing constraints. We also study the cosmological beta functions across all phases and find their interpretation consistent in the context of bouncing and inflationary scenarios while satisfying the pivot scale normalization requirement. Further, we estimate the spectral distortion effects and shed light on controlling PBH overproduction.